Numerical analysis of blast pressure parameters on the vehicle with and without wall as a barrier - Nor Fadliha, Aziz (2019)
Demolition of old structure or building by using explosive is one of the methods are used in construction and development works at an existing location. Unfortunately, this method also preferred by terrorist to gain attention from the local or international authorities. This kind of terrorist attack is lethal when occurred at the place where the authorities not expected to occur for example nearby the residential area including those in the vehicle. So when vehicles are exposed to this explosion, it could have a negative impact on the car's structure thus can also affect the people inside. This is because most of the vehicles are not designed to withstand the dynamic load such as bullet and blast load, and it does offer almost no protection to the occupants inside except to those vehicles for special purpose usage such as for royal and higher ranking government officer. Hence in this study, the blast pressure parameter from the explosion of 13.61 kg (30 lbs.) Trinitrotoluene (TNT) will be evaluated numerically. To achieve this objective, ANSYS AUTODYN will be used to simulate the blast pressure on the surrounding area. The numerical simulation initially conducted in 3D free air explosion of 1000 mm x 1000 mm x 5500 mm volume of air and followed by the consideration of another two different cases by increasing in air domain of 1219 mm x 3000 mm x 1112 mm volume of air. The grid arrangement of I, J, K (18, 22, 72) is considered in both cases which are without any obstruction of the wall and with obstruction of the wall on the blast wave propagation. Before running any simulation, the initial detonation of the explosive is modeled. The validation of 30 lbs. TNT of the gauge located at 5486 mm (18 ft.) from the charge weight will be verified with the actual blast test in previous literature by Yan et. al, (2011). After this verification, the same blast wedge was remapped and used for case 2 and case 3; without and with barrier wall respectively. Then, the numerical result obtained at different position of gauges in case 2 and case 3 is presented and compared. The results show that the peak overpressure for gauge 1 located at 1219 mm away in front of the charge weight for case 3 is instantaneously higher compared to case 2. It is proved that when the wave encounters a surface, it is reflected and magnified the overpressure. Besides that, for gauge 2 located at 1369 mm away from the explosive center where the location for case 3; with wall as a barrier, this gauge is located exactly behind the wall. It shows that overpressure for this gauge in case 3 is lower than in case 2. This is because when a charge from the blast wave impact the barrier wall, it will diffract around the barrier wall. As a result, the wave is lessened for some distance behind the wall. Moreover, the effect of the blast pressure on human inside the vehicle to an overpressure of 250 kPa for case 2 and 220 kPa for case 3, the person may result in threshold of fatalities. For case 2 and case 3, the effect of the blast pressure on human outside the vehicle which it exposed to the highest peak overpressure than the other four gauges about 540 kPa and 510 kPa respectively. So, the person at this location likely to experience 100 % of fatalities. In addition, based on the comparison between two cases which are for case 2 and case 3, it can be concluded that the peak overpressure for case 3 is lower than peak overpressure in case 2. Therefore, for overall results show that the blast pressure reduced when there is barrier wall nearby the blast event compared when there is no wall at blast event.